A novel approach to safety analysis of floating structures experiencing storm. (15th February 2018) - Abaei, Mohammad Mahdi; Arzaghi, Ehsan; Abbassi, Rouzbeh; Garaniya, Vikram; Chai, Shuhong
Abstract: Marine floating structures may experience harsh environmental conditions during their operational life span. In order to maintain a safe operation, it is necessary to evaluate the performance of the structure in extreme conditions such as storm. Previously, various approaches were introduced to analyse the response of an offshore structure in different sea states. However, the proposed methods are computationally time consuming requiring a large number of simulations and it is not the most realistic approach to analyse the dynamic behavior of a structure by separately replicating each level of storm. In this study, a novel numerical model of storm is developed based on Endurance Wave Analysis (EWA) concept. The developed model will reduce the computational cost to only one storm record of 1100 s taking into account the randomness of sea environment. The application of this method is demonstrated by assessing a Floating Storage Unit (FSU) responses encountering a storm in the North Sea. The results show that the response of structure is likely to exceed the survival condition while encountering storm level 10 corresponding to a wave height of 12.56 m. The proposed method is beneficial for future risk and reliability analyses that require a great deal of data. Highlights: Highlighting the advantages of advanced wave model for hydrodynamic analysis of marine structures in harsh environment. Development of a novel methodology for performance analysis of marine structure experiencing storm. Developing an intensifying storm model for assessing the performance of floating structure in harsh environment. Reduction of the simulation time for hydrodynamic analysis of floating structures using Endurance Wave Analysis (EWA) method.